1976
DOI: 10.1104/pp.57.4.589
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ribulose 1,5-Diphosphate Carboxylase in Nonphotosynthetic Endosperms of Germinating Castor Beans

Abstract: Previous reports have described the presence and properties of RuDP2 carboxylase in castor bean endosperms (4, 15). These are the only reports of the occurrence of this enzyme in nonphotosynthetic higher plant tissue. RuDP carboxylase has been localized in the proplastids of germinating castor beans (15) and the enzyme reaches a peak activity in the dark in 4 days (4). Dark-grown etiolated leaves contain low amounts of RuDP carboxylase activity which increases substantially only after exposure of the leaves to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Vol. 59,1977 sperm was substantially similar to that described by Benedict (3,8) and Osmond et al (16). However, as RuDP Case activity declined in the endosperm there was a rapid increase in activity in the cotyledons (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Vol. 59,1977 sperm was substantially similar to that described by Benedict (3,8) and Osmond et al (16). However, as RuDP Case activity declined in the endosperm there was a rapid increase in activity in the cotyledons (Fig.…”
Section: Resultssupporting
confidence: 75%
“…It is also clear that in many species phytochrome action does not regulate the amount of this enzyme. As an extreme example, Gillen et al [15] found that the amount of RuBP carboxylase increased in the dark in the nonphotosynthetic endosperm of germinating castor beans.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative pathway to provide pyruvate for plastidial fatty acid biosynthesis could be via RubisCO. The activity of this enzyme has been demonstrated in the endosperm of germinating castor beans (Benedict, 1973;Osmond et al, 1975;Gillen et al, 1976) and the corresponding protein subunits were found in our plastid proteome (B9SYG1 and G1D766; Figure 9, No. 1).…”
Section: Metabolic Role Of Plastids In Castor Bean Endospermmentioning
confidence: 73%